Applying partial least squares structural equation modelling (PLS-SEM) on factors affecting language students’ desire to learn - Mat Daud, Nor Shidrah; Mat Daud, Nuraihan; Abdul Latif, Samshul Amry; Simpson, Jantima (2022)
This study examines factors affecting students’ desire to learn the English language using Partial Least Squares Structural Equation Modelling (PLS-SEM). This is to explain and predict students’ desire to learn. For this purpose, a questionnaire survey was conducted at two public universities in Malaysia and one in Thailand. The questionnaires were developed based on Gardner’s (2004) Attitude/Motivation Test Battery. Only four subscales of the instrument were chosen for this study. These were: desire to learn, instrumental motivation, foreign language anxiety and attitude towards foreign language. It was found that although Attitude toward Foreign Language, Foreign Language Anxiety and Instrumental Motivation have small predictive relevance on Desire to Learn the English language, they are crucial in explaining the students’ desire to learn the language. The study indicates that the model is sufficiently reliable and consistent. When the groups were compared, the relationship between Instrumental Motivation and Desire to Learn was higher between International Islamic University Malaysia (IIUM) and Universiti Teknologi MARA (UiTM) students but the difference is not significant where IIUM and Naresuan University (NU) students were concerned. This study serves to model a quantitative empirical research method to explain and predict factors affecting desire to learn.